Functional characterization of a putative signalling peptide TAXIMIN in the model plant Arabidopsis thaliana and a medicinal plant Sutherlandia frutescens L. R. Br. - Colling, Janine (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhD)--Stellenbosch University, 2016.